Comparison of the effects in the germination and growth of corn seeds (Zea mays L.) by exposure to magnetic, electrical and electromagnetic fields (2023)
At the moment of obtaining good agricultural yields, as in the specific case of corn (Zea mays L.), the action of various factors, such as the surrounding environment, can cause a decrease of the germinative power of seeds. To improve the germinative power of the corn seeds, it has been searched for new methods and technologies. In this regard, our study focuses on the comparison of the effects on seeds when exposed to magnetic fields of high and low intensities, and to electric and electromagnetic fields. For a time of 15 days the seeds were exposed by different fields. The studied variables were: the germination percentage, growth dynamics of coleoptiles, and accumulation of fresh mass, dry biomass and contents of chlorophyll a, chlorophyll b, and total chlorophyll. The best results were obtained for the seeds treated with electromagnetic fields doubling the value of most of the indicators under study. Copyright © 2015, AIDIC Servizi S.r.l.